Effects of Noradrenergic Stimulation Upon Context-Related Extinction Learning Performance and BOLD Activation in Hippocampus and Prefrontal Cortex Differ Between Participants Showing and Not Showing Renewal - Lissek, Silke; Klass, Anne; Tegenthoff, Martin (Frontiers in Behavioral Neuroscience, 2019)
While the neural structures mediating context-related renewal of extinction are well established, the neurotransmitter systems processing renewal remain elusive. Noradrenergic stimulation before extinction improved learning, but did not alter renewal. Since context processing already during initial conditioning can influence renewal, in this fMRI study we investigated how noradrenergic stimulation by a single dose of atomoxetine (ATO) before initial acquisition of a context-related predictive-learning task affects subsequent learning and renewal in humans. ATO participants showing contextual renewal (REN) exhibited a selective extinction learning deficit compared to placebo (PLAC) and ATO participants lacking renewal (ATO NoREN), probably owing to formation of more stable associations during acquisition. New learning and retrieval during the extinction phase as well as initial acquisition were unimpaired. In ATO REN, higher activation in right inferior frontal gyrus (iFG) during acquisition may have supported the formation of more stable associations, while reduced activation in hippocampus and left iFG during extinction was associated with impaired context encoding and response inhibition. During recall, ATO REN showed reduced overall context-dependent renewal associated with higher activation in medial PFC and right hippocampus. The results demonstrate the importance of noradrenergic processing in inferior frontal cortex and hippocampus for human extinction learning, but not necessarily initial conditioning. Since an identical atomoxetine treatment evoked diverging BOLD activation patterns in REN and NoREN participants, the effect is presumably related to the participants‘ preferred processing strategies that may have recruited differentially interconnected networks in which noradrenergic stimulation produced diverging consequences. In the ATO REN group, probably an additive effect of their preferred processing strategy, which pre-activated the noradrenergic system, and the experimental treatment caused a shift beyond the optimal working range of the noradrenergic system, thus modulating BOLD activation in a way that impaired extinction learning and recall.